Analisis Penerapan Etika Bisnis Islam dalam Transaksi Jual Beli Ikan Basah di Pasar Simpang Tiga Kecamatan Luhak Nan Duo Kabupaten Pasaman Barat - Rahmadani, Nofita; Basir, Gusril (STAI Denpasar Bali, 2024)
This research aims to find out how the application of Islamic business ethics in buying and selling transactions by wet fish traders in the Simpang Tiga market. This research uses descriptive qualitative research methods. This type of descriptive qualitative research is research where the aim is to provide descriptions of a fact, and properties related to the phenomenon being studied. This qualitative research has the aim of producing data in the form of oral words and how behavior is being observed. This research was conducted through direct observation and interviews with market managers as well as fish traders and fish buyers in the Simpang Tiga market, Luhak Nan Duo District, West Pasaman Regency. The results of this study are the implementation of buying and selling wet fish in the Simpang Tiga market carried out by traders on Friday at 07.00 to 18.00. At the time of the implementation of the transaction of buying and selling wet fish, there are still many traders who leave Friday prayers in order to continue trading and cheating by reducing the scales where the average reduction in scales is 0.10-0.15kg. The review of Islamic business ethics in the implementation of buying and selling wet fish in the Simpang Tiga market is not in accordance with the principles of Islamic business ethics, such as the principle of oneness (tawhid), the principle of justice, the principle of honesty, the principle of responsibility and the principle of freedom. The fraud committed by traders aims to get more profit.